2022
DOI: 10.3390/ijerph191811815
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Its Sociodemographic Predictors: A Cross-Sectional Study of a Population in Madrid (Spain)

Abstract: Background: Health literacy enhances a population’s self-care capacity and helps to reduce health inequalities. This work examines the health literacy of a population attending primary care services and explores its relationship with sociodemographic factors. Methods: This cross-sectional study, conducted at a healthcare center in the Madrid region (Spain), involved adult patients requiring primary care nursing services. One hundred and sixty-six participants were recruited via systematic random sampling. Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Because of their greater experience with the healthcare system and their more established relationships with their doctors, older people may be better equipped to handle these challenges. This finding supports those of other investigations [ 58 , 59 ], differing from what was observed in other studies [ 32 , 60 ]. Previously, in examining contradictory findings about the relationship between age and health literacy, van der Heide et al [ 61 ] concluded that age was related to decreased health literacy in various health literacy domains.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Because of their greater experience with the healthcare system and their more established relationships with their doctors, older people may be better equipped to handle these challenges. This finding supports those of other investigations [ 58 , 59 ], differing from what was observed in other studies [ 32 , 60 ]. Previously, in examining contradictory findings about the relationship between age and health literacy, van der Heide et al [ 61 ] concluded that age was related to decreased health literacy in various health literacy domains.…”
Section: Discussionsupporting
confidence: 87%
“…They also outperformed the norm in terms of both the frequency of doctor visits [29] and the consistency with which they implemented their doctors' recommendations. Numerous studies involving a wide range of participants found similar results [29,30]; however, past investigations concluded otherwise [31][32][33]. This disparity may emerge because it is possible that the lack of social and familial assistance for health issues is related to the fact that these individuals tend to live alone.…”
Section: Discussionmentioning
confidence: 94%
“…Older patients may be better suited to dealing with the di culties of the healthcare system because of their greater familiarity with it and their longer history with their physicians. While we do not see this in countries other than KSA [32,33], it is consistent with the results of other studies [34,35]. The ndings of this study have important repercussions for PHC personnel, as they suggest that young adults should be a key focus of any future efforts to improve health literacy.…”
Section: Discussionsupporting
confidence: 90%
“…Based on data from a prior study on health literacy, the sample size was calculated, assuming the population to be infinite [ 11 ]. The present research included 166 subjects.…”
Section: Methodsmentioning
confidence: 99%